The Effect of Training Programs on the Employee Achievment at the UPTP Office in the South Makassar I Region - Hawadi, Muhammad Taufik; Kurniawan, Agung Widhi; Natsir, Uhud Darmawan; Sahabuddin, Romansyah; Dipoatmodjo, Tenri S.P.; Aswar, Nurul Fadilah (Economics and Business Journal (ECBIS), 2023)
This research aims to determine the significance of the effect of training program on the employee achievement at the UPTP Office in the South Makassar Region I 2019-2022. This type of research uses a quantitative approach. The research subjects in this study were 40 employees. The data collection technique used is a questionnaire. The analysis technique used is descriptive statistical analysis with simple linear regression analysis using Statistical for Product and Service Solution (SPSS) software version 16. The results of this research show that training has a positive and significant effect on employee achievment. Employee achievment is directly influenced by the training that occurs at UPTP office in the South Makassar I Region. If the training program is improved, there will be an increase in employee achievement.